Prehospital Mechanical Ventilation: An NAEMSP Position Statement and Resource Document. (4th January 2022) - Baez, Amado Alejandro; Qasim, Zaffer; Wilcox, Susan; Weir, William B.; Loeffler, Patrick; Golden, Bradley Michael; Schwartz, Daniel; Levy, Michael
Abstract: Airway emergencies and respiratory failure frequently occur in the prehospital setting. Patients undergoing advanced airway management customarily receive manual ventilations. However, manual ventilation is associated with hypo- and hyperventilation, variable tidal volumes, and barotrauma, among other potential complications. Portable mechanical ventilators offer an important strategy for optimizing ventilation and mitigating ventilatory complications. EMS clinicians, including those performing emergency response as well as interfacility transports, should consider using mechanical ventilation after advanced airway insertion. Prehospital mechanical ventilation techniques, strategies, and parameters should be disease-specific and should mirror in-hospital best practices. EMS clinicians must receive training in the general principles of mechanical ventilation as well as detailed training in the operation of the specific system(s) used by the EMS agency. Patients undergoing mechanical ventilation must receive appropriate sedation and analgesia.